Queering Public Health: A Critical Examination of Healthcare Access and Gender Expression among Trans, Nonbinary, and Other Gender Nonconforming People during COVID-19. (4th March 2023) - Grey, Cornel; Sinno, Jad; Zhang, Haochuan; Daroya, Emerich; Skakoon-Sparling, Shayna; Klassen, Ben; Lessard, David; Hart, Trevor A.; Cox, Joseph; Stewart, Mackenzie; Grace, Daniel
Abstract : Research documenting the impact of COVID-19 on Two-Spirit, lesbian, gay, bisexual, transgender, and queer (2SLGBTQ+) populations in Canada is limited. Our objectives were to investigate the impact of COVID-19 lockdown measures on the lives of trans, nonbinary, and other gender nonconforming (TGNC) people. Engage COVID-19 is a mixed methods study examining the impact of COVID-19 on gay, bisexual, queer, and other men who have sex with men (GBQM) living in Vancouver, Toronto, and Montreal, Canada. Using purposive sampling, we conducted in-depth qualitative interviews (between November 2020–February 2021 and June–October 2021) with 93 participants who discussed the impact of COVID-19 on their lives. Seventeen participants were identified as TGNC. TGNC participants reported barriers to trans healthcare during the initial months of the COVID-19 pandemic. Several participants indicated that some public health interventions during COVID-19 (i.e., lockdowns) eased the pressure to "perform" gender due to fewer in-person interactions. During lockdowns, TGNC participants increasingly cultivated community networks online. Nevertheless, participants reported longing for the social support that was available to them during pre-COVID. Lack of access to community spaces during lockdowns had a negative impact on participants' mental health, despite reduced pressure to perform gender and opportunities for social engagement in online spaces.